Propagating-path uniformly scanned light sheet excitation microscopy for isotropic volumetric imaging of large specimens - Ping, Junyu (J Biomed Opt, 2019)
We demonstrate a propagating-path uniformly scanned light sheet excitation (PULSE) microscopy based on the oscillation of voice coil motor that can rapidly drive a thin light sheet along its propagation direction. By synchronizing the rolling shutter of a camera with the motion of laser sheet, we can obtain a uniform plane-illuminated image far beyond the confocal range of Gaussian beam. A stable [Formula: see text] optical sectioning under a [Formula: see text] wide field of view (FOV) has been achieved for up to 20 Hz volumetric imaging of large biological specimens. PULSE method transforms the extent of plane illumination from one intrinsically limited by the short confocal range ([Formula: see text] scale) to one defined by the motor oscillation range (mm scale). Compared to the conventional Gaussian light sheet imaging, our method greatly mitigates the compromise of axial resolution and successfully extends the FOV over 100 times. We demonstrate the applications of PULSE method by rapidly imaging cleared mouse spinal cord and live zebrafish larva at isotropic subcellular resolution.